High-temperature-resistant piezoelectric film sensor structure and preparation method and application thereof

By using high-entropy alloy anti-diffusion barrier layer and high-entropy alloy oxide protective layer in piezoelectric sensors, the reliability and life of traditional piezoelectric sensors in high temperature environments is solved, and higher thermal stability and resistance are achieved.

CN119698226AActive Publication Date: 2025-03-25WUHAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510045319.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-25
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Traditional piezoelectric sensors are prone to peeling due to the difference in thermal expansion coefficient between the substrate and the piezoelectric coating in high temperature environments, as well as the diffusion and oxidation of piezoelectric layer elements caused by high temperatures, which reduces the reliability and life of the sensor.

Method used

The anti-diffusion barrier layer composed of high-entropy alloy is located above, below and around the piezoelectric layer. Combined with a protective layer composed of high-entropy alloy oxides, it significantly improves the resistance and thermal stability of the sensor structure.

Benefits of technology

Effectively isolate the air, prevent the diffusion and oxidation of lightweight elements, and significantly improve the high temperature stability and reliability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698226A_ABST
    Figure CN119698226A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant piezoelectric film sensor structure and a preparation method and application thereof, the sensor structure comprises a substrate, a piezoelectric layer, a protective layer and an electrode layer from bottom to top, and the protective layer is made of high-entropy alloy oxide; a first anti-diffusion barrier layer is arranged between the substrate and the piezoelectric layer, and / or a second anti-diffusion barrier layer is also arranged between the piezoelectric layer and the protective layer; the first anti-diffusion barrier layer and the second anti-diffusion barrier layer are made of high-entropy alloy. According to the high-temperature-resistant piezoelectric film sensor structure, the anti-diffusion barrier layer made of the high-entropy alloy is adopted, oxygen atoms are not contained, and diffusion and oxidation speed of light elements in the piezoelectric layer can be well prevented; the protection layer formed by the high-entropy alloy oxide significantly improves the resistance of the sensor structure, can prevent the piezoelectric layer from being broken down in the high-voltage test process, improves the working stability of the sensor structure, and also can improve the high-temperature stability of the sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of intelligent temperature sensors, and in particular to a high-temperature resistant piezoelectric film sensor structure, a preparation method and an application thereof. Background Art

[0002] Ultrasonic measurement technology based on piezoelectric sensors is considered to be a reliable and non-invasive method for testing the health status of key machine components. It is usually composed of a sensor network installed or embedded in the structure of the object to be tested, portable diagnostic hardware and data analysis software. Its core component, the ultrasonic temperature / stress sensor, is based on the acoustic elastic effect. The propagation speed of ultrasonic waves in the bolt is related to the ambient temperature / stress, which causes the flight time and piezoelectric signal to change accordingly. The functional relationship between ultrasonic propagation time, sound wave amplitude and temperature / stress is established, and the correlation coefficient in the functional relationship is obtained through calibration tests. The ambient temperature / stress can be quantitatively calculated by measuring the flight time of ultrasonic waves under different temperature / stress loads, thereby judging the temperature / stress status of machine components. That is, temperature / stress monitoring can be achieved by converting the temperature / stress state into the corresponding ultrasonic signal. It is highly accurate, convenient and efficient, and non-destructive. It is not affected by human, air, surrounding objects and other environmental factors, and can achieve real-time monitoring and remote control.

[0003] Traditional piezoelectric sensors include a piezoelectric layer, a protective layer, a bonding layer, and an electrode layer. The protective layer is usually made of SiO2, and its main function is to prevent the piezoelectric layer from being broken down during high-voltage testing. In high-temperature environments, traditional piezoelectric sensors are prone to peeling due to the difference in thermal expansion coefficients between the substrate and the piezoelectric coating. At the same time, high temperatures can easily damage the piezoelectric layer, such as element diffusion and oxidation, reducing the reliability and life of the entire sensor.

[0004] Therefore, it is necessary to improve the structure of the piezoelectric sensor to improve the high temperature resistance of the sensor. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a high temperature resistant piezoelectric film sensor structure, which includes a substrate, a piezoelectric layer, a protective layer and an electrode layer from bottom to top, wherein the material of the protective layer is a high entropy alloy oxide; A first anti-diffusion barrier layer is provided between the substrate and the piezoelectric layer, and / or a second anti-diffusion barrier layer is provided between the piezoelectric layer and the protective layer; The first anti-diffusion barrier layer and the second anti-diffusion barrier layer are made of high entropy alloy.

[0006] Furthermore, the thickness of the protective layer is 4-10 μm; The thickness of the first anti-diffusion barrier layer and the second anti-diffusion barrier layer is 1-10 μm.

[0007] Further, the alloying elements of the high entropy alloy oxide and the high entropy alloy include at least eight of Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W, Y, and Si. Corresponding to these alloying elements, illustratively, the materials of the first diffusion barrier layer and the second diffusion barrier layer can both be or independently selected from at least one of TiVCrZrNbMoHfTaWAlSiY, TiVCrZrNbMoHfTaWAlSi, AlCrNbSiTaTiVZr, and AlMoNbSiTaTiVZr. It should be noted that the present invention represents the high entropy alloy oxide with the general formula of XO, wherein X represents the high entropy alloy, and correspondingly, the material of the protective layer can be at least one of TiVCrZrNbMoHfTaWAlSiY-O, TiVCrZrNbMoHfTaWAlSi-O, AlMoNbSiTaTiVZr-O, and AlMoNbSiTaTiVZr-O.

[0008] Furthermore, the thickness of the piezoelectric layer is 5-25 μm.

[0009] Furthermore, the material of the electrode layer is a solid metal element or a solid metal alloy with a thickness of 2-20 μm.

[0010] Furthermore, the electrode layer is divided into an inner electrode region and an outer electrode region.

[0011] It should be noted that in the present invention, the substrate does not need to be strictly limited, and illustratively, it can be a stainless steel plate, a silicon wafer, a bolt, etc. The material of the medium piezoelectric layer does not need to be strictly limited, and illustratively, it can be LiNbO3, AlN, ZnO, and metal-doped LiNbO3, AlN, ZnO, etc. The material of the electrode layer does not need to be strictly limited, and illustratively, it can be at least one of a metal single substance such as Ag, Cr, Ti, or an alloy such as AgCr, a high entropy alloy, etc.

[0012] The present invention also provides a method for preparing a high temperature resistant piezoelectric film sensor structure, comprising: A piezoelectric layer, a protective layer and an electrode layer are sequentially prepared on the substrate surface, wherein the piezoelectric layer is also prepared after the first anti-diffusion barrier layer is prepared on the substrate surface, and / or, Preparing a second anti-diffusion barrier layer and a protective layer on the surface of the piezoelectric layer; The material of the protective layer is a high entropy alloy oxide, and the material of the first anti-diffusion barrier layer and the second anti-diffusion barrier layer are high entropy alloys.

[0013] Furthermore, the first anti-diffusion barrier layer, the piezoelectric layer, the second anti-diffusion barrier layer, the protective layer, and the electrode layer are all prepared by radio frequency magnetron sputtering. The parameters of the radio frequency magnetron sputtering method specifically include: The first anti-diffusion barrier layer and the second anti-diffusion barrier layer: input pure Ar, total gas flow rate 1.1-2.5Pa, RF power 750-900W, temperature 40-150℃, target-base distance 8.5-15cm, time 10min-60min; For different types of piezoelectric coatings, the parameters of RF magnetron sputtering are different. For example, for the oxide piezoelectric layer, the target-substrate distance is 4cm-10cm, Ar and O2 are input, the total gas flow rate is 0.8-2.1Pa, the Ar / O2 flow ratio is 1 / 1-6 / 1, the RF power is 800-900W, the bias voltage is 0-30V, and the coating time is 4-10h; for the nitride piezoelectric layer, the target-substrate distance is 6cm-12cm, Ar and N2 are input, the total gas flow rate is 0.8-2.1Pa, the Ar / O2 flow ratio is 1 / 1-3 / 1, the RF power is 800-900W, and the coating time is 4-10h; Protective layer: input pure Ar and O2, total gas flow rate 1.1-2.5Pa, Ar / O2 flow ratio 1.1 / 1-3 / 1, RF power 750-900W, temperature 40-150℃, target-base distance 8.5-15cm, time 5.5h-7h; Electrode layer: input pure Ar, total gas flow rate 1.1-2.5Pa, RF power 750-900W, temperature 40-150℃, target-base distance 5-10cm, time 30min-2h.

[0014] Furthermore, arc etching is used for surface treatment before the preparation of the first diffusion barrier layer, the piezoelectric layer, the second diffusion barrier layer, the protective layer, and the electrode layer. Arc etching for surface treatment can remove pollutants such as oil and dust on the surface of the substrate and enhance the bonding performance between layers. The arc etching technology uses Cr target material, passes 0.5Pa-2.0Pa pure Ar gas, the etching voltage is 100V-200V, the duty cycle is 20%-70%, and the current is 2.0A-4.0A. The etching time before preparing the first diffusion barrier layer is 5min-10min, and the other etching times are 1min-5min.

[0015] Preferably, after the protective layer is prepared, an insulating ring is pasted on the surface of the protective layer. When the electrode layer is subsequently prepared, the electrode layer can be formed into an inner electrode area and an outer electrode area due to the presence of the internal insulating ring, which facilitates ultrasonic signal testing.

[0016] The present invention also provides a temperature detection system, comprising the above-mentioned sensor structure.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The sensor structure prepared by the present invention adopts an anti-diffusion barrier layer composed of a high entropy alloy, which can be located above, below and around the piezoelectric layer to isolate the air to the greatest extent. The anti-diffusion barrier layer adopts a pure metal layer and does not contain oxygen atoms, which can effectively prevent the escape and diffusion of lightweight elements, greatly reducing the diffusion and oxidation rate of lightweight elements in a high temperature environment.

[0018] The sensor structure prepared by the present invention adopts a protective layer composed of high entropy alloy oxide, which is located above and around the piezoelectric layer, significantly improving the resistance of the sensor structure. It can not only prevent the piezoelectric layer from being broken down during high voltage testing and improve the working stability of the sensor structure in a high voltage environment, but also serve as a high temperature protective layer to improve the high temperature stability of the sensor structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 A schematic diagram of the structure of a high temperature resistant piezoelectric film sensor prepared by the technology of the present invention is shown, in which: 1, substrate; 2, first anti-diffusion barrier layer; 3, piezoelectric layer; 4, second anti-diffusion barrier layer; 5, protective layer; 6, electrode layer; Figure 2 The cross-sectional morphology of the sensor structure prepared in Example 1 is shown; Figure 3 The cross-sectional element distribution of the sensor structure prepared in Example 1 is shown; Figure 4 The surface morphology and element distribution of each layer of the sensor structure prepared in Example 1 are shown; Figure 5 The ultrasonic signal test diagram of the sensor prepared in Example 1 after annealing at 760° C. for different time periods is shown; Figure 6 The ultrasonic signal and piezoelectric constant d of the sensor structure prepared in Example 1 after annealing at 760°C for different times are shown. 33 Test results; Figure 7 The relative changes of ultrasonic signals of the sensors prepared in Example 1 and Comparative Example 1 after annealing at 760° C. for different time periods are shown; Figure 8 The piezoelectric constants d of the sensors prepared in Example 1 and Comparative Example 1 after annealing at 760°C for different times are shown. 33 relative changes in Fig. 9 The ultrasonic signal and piezoelectric constant d of the sensor prepared in Example 4 after annealing at 400°C, 500°C, 600°C, and 700°C for 1 h are shown. 33 Result graph; Fig.10 The relative changes of ultrasonic signals of the sensors prepared in Example 4, Example 5, Example 6, Comparative Example 5 and Comparative Example 6 after annealing at 400° C., 500° C., 600° C. and 700° C. for 1 h are shown; Fig.11 The piezoelectric constants d of the sensors prepared in Example 4, Example 5, Example 6, Comparative Example 5 and Comparative Example 6 after annealing at 400°C, 500°C, 600°C and 700°C for 1h are shown. 33 relative changes in Fig.12 The Raman spectra of the LiNbO3 piezoelectric layers of the sensors prepared in Example 1 and Comparative Example 3 before and after annealing at 760°C for 10 hours are shown. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0022] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1 A method for preparing a high temperature resistant piezoelectric film sensor structure, the steps are as follows: Step 1: preparing the first anti-diffusion barrier layer 2: (1) Prepare TiVCrZrNbMoHfTaWAlSiY high entropy alloy target and clean stainless steel substrate 1, and install them in a radio frequency magnetron sputtering coating machine with a target-substrate distance of 10 cm and a vacuum degree of 4×10 -3 Pa; (2) Arc etching technology is used to carry out etching to remove pollutants such as oil and dust on the surface of the substrate 1 and enhance the bonding performance between the first diffusion barrier layer 2 and the substrate 1. The arc etching technology uses a Cr target material and etches for 9 minutes under a 1.1Pa pure Ar gas atmosphere, an etching voltage of 150V, a duty cycle of 60%, and a current of 3.0A; (3) Wait until the vacuum degree reaches 4×10 -3 Pa, pure Ar was input, and the deposition was carried out for 60 minutes at a total gas flow rate of 1.1 Pa, a radio frequency power of 750 W, a temperature of 80° C., and a target-substrate distance of 10 cm to obtain a first anti-diffusion barrier layer 2 with a thickness of about 5.5 μm.

[0024] Step 2: Prepare the piezoelectric layer 3: (1) Prepare lithium niobate target and install it in a radio frequency magnetron sputtering coating machine with a target-base distance of 4.5 cm and a vacuum degree of 5×10 -3 Pa; (2) Arc etching technology is used to carry out etching to enhance the bonding performance between the piezoelectric layer and the first diffusion barrier layer. Arc etching technology uses Cr target material, and etches for 1 minute under 1.1Pa pure Ar gas atmosphere, etching voltage 150V, duty cycle 60%, and current 3.0A; (3) Wait until the vacuum degree reaches 4×10 -3 Pa, input Ar and O2, and deposit for 8.5 hours at a total gas flow rate of 0.8 Pa, an Ar / O2 flow ratio of 6 / 1, an RF power of 900 W, a temperature of 80°C, and a bias voltage of 7 V to obtain a piezoelectric layer 3 with a thickness of about 36 μm.

[0025] Step 3: preparing the second anti-diffusion barrier layer 4: (1) Prepare TiVCrZrNbMoHfTaWAlSiY high entropy alloy target and install it in a radio frequency magnetron sputtering coating machine with a target-substrate distance of 10 cm and a vacuum degree of 4×10 -3 Pa; (2) Arc etching technology is used to carry out etching to enhance the bonding performance between the second diffusion barrier layer 4 and the piezoelectric layer 3. Arc etching technology uses Cr target material, and the etching is carried out for 2 minutes under 1.1Pa pure Ar gas atmosphere, etching voltage 150V, duty cycle 60%, and current 3.0A; (3) Wait until the vacuum degree reaches 4×10 -3 Pa, pure Ar was input, and the deposition was carried out for 60 minutes at a total gas flow rate of 1.1 Pa, a radio frequency power of 750 W, a temperature of 80° C., and a target-substrate distance of 10 cm to obtain a second anti-diffusion barrier layer 4 with a thickness of about 5.5 μm.

[0026] Step 4, following step 3, preparing a protective layer 5: (1) Prepare TiVCrZrNbMoHfTaWAlSiY high entropy alloy target and clean stainless steel substrate, and install them in a radio frequency magnetron sputtering coating machine with a target-substrate distance of 10 cm and a vacuum degree of 4×10 -3 Pa; (2) Arc etching technology is used to carry out etching to enhance the bonding performance between the protective layer 5 and the second diffusion barrier layer 4. The arc etching technology uses a Cr target material and etches for 1 minute in a 1.1Pa pure Ar gas atmosphere, an etching voltage of 150V, a duty cycle of 60%, and a current of 3.0A; (3) Wait until the vacuum degree reaches 4×10 -3 Pa, input Ar and O2, deposit for 5.5 hours at a total gas flow rate of 1.1 Pa, an Ar / O2 flow ratio of 1.1 / 1, an RF power of 750 W, a temperature of 80 ° C, and a target-substrate distance of 10 cm to obtain a protective layer 5 with a thickness of about 4.5 μm; Step 5: Paste an insulating ring on the surface of the protective layer 5. The purpose of the insulating ring is to form inner and outer electrode areas for easy ultrasonic signal testing. The insulating ring is made of polyester amide, 0.15 mm thick, with an inner ring diameter of 3 mm and an outer ring diameter of 5 mm.

[0027] Step 6: Prepare electrode layer 6: (1) Prepare AgCr target (Ag / Cr atomic ratio is 2 / 1) and install it in a radio frequency magnetron sputtering coating machine with a target-substrate distance of 8 cm and a vacuum degree of 4×10 -3 Pa; (2) Arc etching technology is used to carry out etching to enhance the bonding performance between the electrode layer 6 and the protective layer 5. The arc etching technology uses a Cr target material and etches for 2 minutes in a 1.1Pa pure Ar gas atmosphere, an etching voltage of 150V, a duty cycle of 60%, and a current of 3.0A; (2) Wait until the vacuum degree reaches 4×10 -3 Pa, input Ar, deposit for 1 h at a total gas flow rate of 1.1 Pa, RF power of 750 W, temperature of 80 ° C, and a target-substrate distance of 8 cm to obtain an electrode layer 6 with a thickness of about 6.0 μm; (3) When the temperature in the chamber is lower than 50°C, take out the Figure 1 The high temperature resistant piezoelectric film sensor structure is shown.

[0028] The cross-sectional morphology of the high temperature resistant piezoelectric film sensor structure prepared in Example 1 was observed by scanning electron microscopy. Figure 2 As shown in Figure 2, HEA and HEAO represent high entropy alloy and high entropy alloy oxide, respectively. Figure 1 The results show that the prepared high temperature resistant piezoelectric film sensor has uniform structure and stability. Figure 3The cross-sectional element distribution of the high temperature resistant piezoelectric film sensor structure is shown, and it can be seen that the elements in each layer are evenly distributed. Figure 4 The surface morphology and element distribution of each layer of the high temperature resistant piezoelectric film sensor structure are shown. It can be seen that the surface morphology of each layer is uniform and the element distribution is uniform.

[0029] Comparative Example 1 Compared with Example 1, the difference is that: Step 1, Step 3 and Step 4 do not exist, that is, the electrode layer is directly prepared after the piezoelectric layer is deposited on the surface of the stainless steel substrate to obtain the sensor structure.

[0030] Comparative Example 2 Compared with Example 1, the difference is that: there is no step 4, that is, after the first anti-diffusion barrier layer, the piezoelectric layer, and the second anti-diffusion barrier layer are sequentially prepared on the substrate, the electrode layer is prepared to obtain the sensor structure.

[0031] Comparative Example 3 Compared with Example 1, the difference is that: Step 1 and Step 3 do not exist, that is, the piezoelectric layer, the protective layer and the electrode layer are prepared in sequence on the substrate to obtain the sensor structure.

[0032] Comparative Example 4 Compared with Example 1, the difference is that: Step 1, Step 3, Step 4 and Step 5 do not exist, that is, the piezoelectric layer is directly deposited on the surface of the stainless steel substrate to obtain the sensor structure.

[0033] After the sensor structures prepared in Example 1 and Comparative Example 1 were annealed at 760° C. for 10 h, 20 h, 40 h, and 100 h, the ultrasonic signal and the piezoelectric constant d were tested at an excitation voltage of 100 V and a gain of 20 dB. 33 .from Figure 5 and Figure 6 It can be seen that during the long annealing process at 760°C for 100 h, the longitudinal wave signals of the sensor structure of Example 1 are 0.50 V, 0.43 V, 0.36 V, and 0.31 V respectively when the annealing time is 10 h, 20 h, 40 h, and 100 h, and the piezoelectric constant d 33 They are 4.5pC / N, 4.3pC / N, 4.0pC / N, and 3.5pC / N respectively. Figure 7 and Figure 8 It can be seen that during the long annealing process at 760°C for 100 h, the sensor structure prepared in Example 1 has a higher longitudinal wave signal and a piezoelectric constant d than that in Comparative Example 1. 33 The decline rate is obviously slower, which indicates that the presence of the first / second anti-diffusion barrier layer and the protective layer effectively improves the thermal stability of the sensor.

[0034] Example 2-3 Compared with Example 1, the difference is that in step 4, the deposition time in preparing the protective layer is 7 h and 10 h respectively, and the protective layers with thicknesses of approximately 6.0 μm and 8.5 μm are obtained respectively.

[0035] Example 4 Compared with Example 1, the difference is that in step 2, a vanadium-doped lithium niobate target is used, and the vanadium doping amount is 1.8%. The corresponding magnetron sputtering parameters are: when the vacuum degree reaches 4×10 -3 Pa, input Ar and O2, and deposit for 7 hours at a total gas flow rate of 0.9Pa, an Ar / O2 flow ratio of 6 / 1, an RF power of 900W, a temperature of 120℃, and a bias voltage of 7V to obtain a piezoelectric layer with a thickness of about 16μm.

[0036] Example 5 Compared with Example 4, the difference is that: there is no step 1, that is, preparing a piezoelectric layer, a second anti-diffusion barrier layer, a protective layer and an electrode layer in sequence on a stainless steel substrate to obtain a sensor structure.

[0037] Example 6 Compared with Example 4, the difference is that: there is no step three, that is, preparing the first anti-diffusion barrier layer, the piezoelectric layer, the protective layer and the electrode layer in sequence on the stainless steel substrate to obtain the sensor structure.

[0038] Comparative Example 5 Compared with Example 4, the difference is that: there is no step 4, that is, preparing the first anti-diffusion barrier layer, the piezoelectric layer, the second anti-diffusion barrier layer and the electrode layer in sequence on the stainless steel substrate to obtain the sensor structure.

[0039] Comparative Example 6 Compared with Example 4, the difference is that: Step 1, Step 3 and Step 4 do not exist, that is, the electrode layer is directly prepared after the piezoelectric layer is deposited on the surface of the stainless steel substrate to obtain the sensor structure.

[0040] After the sensor structures prepared in Example 4, Example 5, Example 6 and Comparative Example 5, Comparative Example 6 were annealed at 400°C, 500°C, 600°C, and 700°C for 1 h, the ultrasonic signal and the piezoelectric constant d were tested at an excitation voltage of 100 V and a gain of 20 dB. 33 .from Fig. 9 It can be seen from the figure that at the same time, as the annealing temperature increases, the longitudinal wave signal and piezoelectric constant d of the sensor structure of Example 4 33 It shows a downward trend. Before annealing, the longitudinal wave signal is 0.7V and the piezoelectric constant d 33is 11.9pC / N. When annealed at 400℃, 500℃, 600℃, and 700℃ for 1h, the longitudinal wave signals are 0.68V, 0.62V, 0.60V, and 0.52V, respectively. The piezoelectric constant d 33 They are 11.6pC / N, 11.2pC / N, 10.9pC / N, and 9.2pC / N respectively. Fig.10 and Fig.11 It can be seen that during the annealing process at 400℃-700℃, the longitudinal wave signal and the piezoelectric constant d 33 The decreasing speeds from slow to fast are as follows: Example 4, Example 5, Example 6, Comparative Example 5, Comparative Example 6, that is, the longitudinal wave signal and piezoelectric constant d of the sensor structure prepared in Example 4 33 The decline rate is the slowest, which indicates that the existence of the first / second anti-diffusion barrier layer and the protective layer effectively improves the thermal stability of the sensor.

[0041] At a measurement frequency of 100 Hz, the resistance of the sensor structures prepared in some embodiments and comparative examples was tested. The results are shown in Table 1.

[0042] Table 1 Resistance test results

[0043] It can be seen from the test results in Table 1 that the protective layer composed of the high entropy alloy oxide TiVCrZrNbMoHfTaWAlSiY-O increases the resistance of the sensor structure. Higher resistance can prevent the piezoelectric layer from being broken down during the high voltage test and improve the working stability of the sensor structure in a high voltage environment.

[0044] The sensor structures prepared in Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 were subjected to Raman and EDS element tests, and then annealed at 760° C. for 10 h, and then subjected to Raman and EDS element tests again.

[0045] For Example 1, the piezoelectric layer (hereinafter referred to as LiNbO3 coating) at a distance of 0.5 μm from the second diffusion barrier layer was selected for Raman and EDS element testing; for Comparative Example 3, the LiNbO3 coating at a distance of 0.5 μm from the protective layer was selected for Raman and EDS element testing. The Raman test results are shown in Figure 2. Fig.12As shown, the Raman peak of the LiNbO3 coating of Example 1 did not change before and after annealing, that is, the LiNbO3 content was stable; while the Raman peaks at positions 156, 237, and 625 of the LiNbO3 coating of Comparative Example 3 all decreased after annealing, which means that the LiNbO3 content decreased. It was measured that the O / Nb atomic ratios of the LiNbO3 coating of Example 1 were 2.83 and 2.81 before and after annealing, which was almost unchanged, that is, the LiNbO3 content was stable; while the O / Nb atomic ratios of the LiNbO3 coating of Comparative Example 3 were 2.82 and 2.69 before and after annealing, and the O / Nb atomic ratio decreased significantly. The decrease in the LiNbO3 content in the Raman spectrum of Comparative Example 3 and the decrease in the O / Nb atomic ratio in the EDS mean that the Li element in the LiNbO3 coating diffuses to the upper coating, and part of the LiNbO3 is transformed into the lithium-deficient phase LiNb3O8, which also shows that the protective layer composed of the high entropy alloy oxide TiVCrZrNbMoHfTaWAlSiY-O in Comparative Example 3 cannot be used as an anti-diffusion barrier layer. The Raman and EDS element test data of Example 1 prove that the second anti-diffusion barrier layer composed of the high entropy alloy TiVCrZrNbMoHfTaWAlSiY is indispensable and can effectively prevent the Li element in the LiNbO3 coating from diffusing to the upper protective layer.

[0046] Similarly, for the sample of Example 1, the LiNbO3 coating at 0.5 μm away from the first diffusion barrier layer was selected for Raman and EDS element testing; for the sample of Comparative Example 3, the LiNbO3 coating at 0.5 μm away from the substrate was selected for Raman and EDS element testing. The test results are consistent with the above. The Raman peak of the LiNbO3 coating of Example 1 did not change before and after annealing, while the Raman peaks at 156, 237, and 625 of the LiNbO3 coating of Comparative Example 3 decreased after annealing; it was measured that the O / Nb atomic ratio of the LiNbO3 coating of Example 1 was almost unchanged before and after annealing, while the O / Nb atomic ratio of the LiNbO3 coating of Comparative Example 3 decreased significantly before and after annealing. The decrease in the LiNbO3 content in the Raman spectrum of Comparative Example 3 and the decrease in the O / Nb atomic ratio in EDS mean that the Li element in the LiNbO3 coating diffuses to the substrate, and part of the LiNbO3 is transformed into the lithium-deficient phase LiNb3O8. The Raman and EDS element test data of Example 1 prove that the anti-diffusion barrier layer composed of the high entropy alloy TiVCrZrNbMoHfTaWAlSiY is indispensable and can effectively prevent the Li element in the LiNbO3 coating from diffusing into the substrate.

[0047] Similarly, for the sample of Example 1, the LiNbO3 coating at 0.5 μm away from the second diffusion barrier layer was selected for Raman and EDS element testing, and for the sample of Comparative Example 1, the LiNbO3 coating at 0.5 μm away from the AgCr electrode layer was selected for Raman and EDS element testing. The test results are consistent with the above. The Raman peak of the LiNbO3 coating of Example 1 did not change before and after annealing, while the Raman peaks at 156, 237, and 625 of the LiNbO3 coating of Comparative Example 1 decreased after annealing; it was measured that the O / Nb atomic ratio of the LiNbO3 coating of Example 3 was almost unchanged before and after annealing, while the O / Nb atomic ratio of the LiNbO3 coating of Comparative Example 1 decreased significantly before and after annealing. The decrease in the LiNbO3 content in the Raman spectrum of Comparative Example 1 and the decrease in the O / Nb atomic ratio in the EDS mean that the Li element in the LiNbO3 coating diffuses to the upper coating, and part of the LiNbO3 is transformed into the lithium-deficient phase LiNb3O8, which also shows that the AgCr electrode layer of Comparative Example 1 cannot be used as an anti-diffusion barrier layer. The Raman and EDS element test data of Example 1 prove that the TiVCrZrNbMoHfTaWAlSiY anti-diffusion barrier layer is indispensable and can effectively prevent the Li element in the LiNbO3 coating from diffusing to the upper electrode layer.

[0048] Similarly, for Example 1, the LiNbO3 coating at 0.5 μm away from the second diffusion barrier layer was selected for Raman and EDS element testing, and for the sample of Comparative Example 4, the position at 0.5 μm away from the surface of the LiNbO3 coating was selected for Raman and EDS element testing. The test results are consistent with the above. The Raman peak of the LiNbO3 coating of Example 1 did not change before and after annealing, while the Raman peaks at positions 156, 237, and 625 of the LiNbO3 coating of Comparative Example 4 all showed a decrease after annealing; it was measured that the O / Nb atomic ratio of the LiNbO3 coating of Example 1 was almost unchanged before and after annealing, while the O / Nb atomic ratio of the LiNbO3 coating of Comparative Example 4 decreased significantly before and after annealing. The decrease in the LiNbO3 content in the Raman spectrum of Comparative Example 4 and the decrease in the O / Nb atomic ratio in EDS mean that the Li element in the LiNbO3 coating diffuses into the air, and part of the LiNbO3 is transformed into the lithium-deficient phase LiNb3O8. The Raman and EDS element test data of Example 1 prove that the TiVCrZrNbMoHfTaWAlSiY anti-diffusion barrier layer is indispensable and can effectively prevent the Li element in the LiNbO3 coating from diffusing into the air.

[0049] It can be seen that the first / second anti-diffusion barrier layer composed of the high entropy alloy TiVCrZrNbMoHfTaWAlSiY in Example 1 can well prevent the Li element from escaping and diffusing into the substrate and the upper coating or the air, greatly reducing the diffusion and oxidation rate of the Li element in a high temperature environment, so that the LiNbO3 content is stable. It also shows that the high entropy alloy oxide protective layer composed of TiVCrZrNbMoHfTaWAlSiY-O cannot serve as a Li element anti-diffusion barrier layer because it is an oxide, and the O atoms it contains will combine with the Li atoms of the LiNbO3 coating. Therefore, the high entropy alloy anti-diffusion barrier layer must be deposited between the high entropy alloy oxide protective layer and the LiNbO3 coating.

[0050] Embodiment 7-9 Compared with Example 1, the difference is that the targets used in step 4 are TiVCrZrNbMoHfTaWAlSi, AlCrNbSiTaTiVZr, and AlMoNbSiTaTiVZr respectively.

[0051] The resistance and ultrasonic signal of the sensor structures constructed in Examples 7 to 9 were also tested, and they had similar performance to that of Example 1. These results show that the present invention uses a high entropy alloy oxide protective layer, which significantly improves the sensor resistance, can not only prevent the piezoelectric layer from being broken down during high voltage testing, improve the working stability of the sensor in a high voltage environment, but also serve as a high temperature protective layer to improve the high temperature stability of the sensor.

[0052] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature resistant piezoelectric film sensor structure, comprising a substrate, a piezoelectric layer, a protective layer and an electrode layer from bottom to top, characterized in that: The material of the protective layer is high entropy alloy oxide; A first anti-diffusion barrier layer is provided between the substrate and the piezoelectric layer, and / or a second anti-diffusion barrier layer is provided between the piezoelectric layer and the protective layer; The first anti-diffusion barrier layer and the second anti-diffusion barrier layer are made of high entropy alloy.

2. The high temperature resistant piezoelectric film sensor structure according to claim 1, characterized in that: The thickness of the protective layer is 4-10 μm; The thickness of the first anti-diffusion barrier layer and the second anti-diffusion barrier layer is 1-10 μm.

3. The sensor structure according to claim 1, characterized in that: The high entropy alloy oxide and the alloying elements of the high entropy alloy include at least eight of Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W, Y, and Si.

4. The sensor structure according to claim 1, characterized in that: The thickness of the piezoelectric layer is 5-50 μm.

5. The sensor structure according to claim 1, characterized in that: The material of the electrode layer is a solid metal element or a solid metal alloy with a thickness of 2-20 μm.

6. The sensor structure according to claim 5, characterized in that: The electrode layer is divided into an inner electrode region and an outer electrode region.

7. A method for preparing a high temperature resistant piezoelectric film sensor structure, characterized in that: include, A piezoelectric layer, a protective layer and an electrode layer are sequentially prepared on the substrate surface, wherein the piezoelectric layer is also prepared after the first anti-diffusion barrier layer is prepared on the substrate surface, and / or, Preparing a second anti-diffusion barrier layer and a protective layer on the surface of the piezoelectric layer; The material of the protective layer is a high entropy alloy oxide, and the material of the first anti-diffusion barrier layer and the second anti-diffusion barrier layer are high entropy alloys.

8. The method for preparing a high temperature resistant piezoelectric film sensor structure according to claim 7, characterized in that: The first anti-diffusion barrier layer, the piezoelectric layer, the second anti-diffusion barrier layer, the protective layer and the electrode layer are all prepared by radio frequency magnetron sputtering.

9. The method for preparing a high temperature resistant piezoelectric film sensor structure according to claim 7, characterized in that: Before the first anti-diffusion barrier layer, the piezoelectric layer, the second anti-diffusion barrier layer, the protective layer and the electrode layer are prepared, arc etching is used for surface treatment.

10. A temperature detection system, characterized in that: The sensor structure comprises the sensor structure according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • High-entropy alloy diffusion barrier layer for Cu interconnect integrated circuit and preparation method of high-entropy alloy diffusion barrier layer for Cu interconnect integrated circuit

    CN108336062A

  • Copper interconnection structure of self-formed high-entropy alloy diffusion barrier layer and preparation method of copper interconnection structure

    CN115172263A

  • Negative temperature sensor, preparation method and detection device

    CN118111582A

  • Corrosion-resistant and high-temperature-resistant electrode material for ultrasonic sensor and preparation method thereof

    CN118329252A

  • Method for forming metal-line of the semiconductordevice using dual damascene process

    KR1020050009799A